HypoxamiRs Profiling Identify miR-765 as a Regulator of the Early Stages of Vasculogenic Mimicry in SKOV3 Ovarian Cancer Cells - Salinas-Vera, Yarely M.; Gallardo-Rincón, Dolores; García-Vázquez, Raúl; Hernández-de la Cruz, Olga N.; Marchat, Laurence A.; González-Barrios, Juan Antonio; Ruíz-García, Erika; Vázquez-Calzada, Carlos; Contreras-Sanzón, Estefanía; Resendiz-Hernández, Martha; Astudillo-de la Vega, Horacio; Cruz-Colin, José L.; et al. (Frontiers in Oncology, 2019)
Vasculogenic mimicry (VM) is a novel cancer hallmark in which malignant cells develop matrix-associated 3D tubular networks with a lumen under hypoxia to supply nutrients needed for tumor growth. Recent studies showed that microRNAs (miRNAs) may have a role in VM regulation. In this study, we examined the relevance of hypoxia-regulated miRNAs (hypoxamiRs) in the early stages of VM formation. Data showed that after 48 h hypoxia and 12 h incubation on matrigel SKOV3 ovarian cancer cells undergo the formation of matrix-associated intercellular connections referred hereafter as 3D channels-like structures, which arose previous to the apparition of canonical tubular structures representative of VM. Comprehensive profiling of 754 mature miRNAs at the onset of hypoxia-induced 3D channels-like structures showed that 11 hypoxamiRs were modulated (FC>1.5; p<0.05) in SKOV3 cells (9 downregulated and 2 upregulated). Bioinformatic analysis of the set of regulated miRNAs showed that they might impact cellular pathways related with tumorigenesis. Moreover, overall survival analysis in a cohort of ovarian cancer patients (n=485) indicated that low miR-765, miR-193b, miR-148a and high miR-138 levels were associated with worst patients outcome. In particular, miR-765 was severely downregulated after hypoxia (FC<32.02; p<0.05), and predicted to target a number of protein-encoding genes involved in angiogenesis and VM. Functional assays showed that ectopic restoration of miR-765 in SKOV3 cells resulted in a significant inhibition of hypoxia-induced 3D channels-like formation that was associated with a reduced number of branch points and patterned tubular-like structures. Mechanistic studies confirmed that miR-765 decreased the levels of VEGFA, AKT1 and SRC-α transducers and exerted a negative regulation of VEGFA by specific binding to its 3`UTR. Finally, overall survival analysis of a cohort of ovarian cancer patients (n=1435) indicates that high levels of VEGFA, AKT1 and SRC-α and low miR-765 expression were associated with worst patients outcome. In conclusion, here we reported a novel hypoxamiRs signature which constitutes a molecular guide for further clinical and functional studies on the early stages of VM. Our data also suggested that miR-765 coordinates the formation of 3D channels-like structures through modulation of VEGFA/AKT1/SRC-α axis in SKOV3 ovarian cancer cells.